Qualitative Research in Social Sciences. About the Need of Methodological Imagination - Malewski, Mieczysław (INSTED: Interdisciplinary Studies in Education & Society, 2017)
In the first part of the article the origin of science methodology is presented and its privileged position among social sciences in the modernism era is explained. The second part presents the development of qualitative research and analyses the effects which are caused by its growing popularity among the social researchers. In the author?s opinion, those processes are the proof of the increase in research individualization and personalisation, which can be interpreted as the announcement of the end of the normative methodology. It can be an indicator of the fact that social sciences enter the post-methodology phase.